Hello, sward071!
I assume you want: \(\displaystyle \:\sqrt{3 - \frac{1}{2}i}\)
Let \(\displaystyle a\, +\, bi \:=\:\sqrt{3\,-\,\frac{1}{2}i\,}\)
where \(\displaystyle a\) and \(\displaystyle b\) are real, and \(\displaystyle a\,>\,0.\) Then:
\(\displaystyle (a\,+\,bi)^2 \;=\;3\, -\, \frac{1}{2}i\)
\(\displaystyle (a^2\,-\,b^2)\, +\, (2ab)i \;=\;3 \,-\, \frac{1}{2}i\)
We have:
\(\displaystyle \begin{Bmatrix}a^2-b^2 &=&3 & [1]
\\ 2ab &=& -\frac{1}{2} & [2] \end{Bmatrix}\)
From [2]: \(\displaystyle b \:=\:-\dfrac{1}{4a}\;\;[3]\)
Substitute into [1]:
\(\displaystyle a^2\,- \,\dfrac{1}{16a^2}\;=\;3\)
And we have:
\(\displaystyle 16a^4\, - \,48a^2 \,\pm\, 1 \;=\;0\)
Quadratic Formula:
\(\displaystyle a^2\;=\;\dfrac{48\, \pm\,\sqrt{2368\,}}{32} \;=\; \dfrac{48 \,\pm \,8\sqrt{37\,}}{32}\)
\(\displaystyle a^2 \;=\;\dfrac{6\, \pm\,\sqrt{37\,}}{4} \quad\,\Rightarrow\,\quad a \;=\;\dfrac{\sqrt{\sqrt{37\,}\,+\,6}}{2} \)
Substitute into [3]:
\(\displaystyle b \;=\;-\dfrac{\sqrt{\sqrt{37\,}\, -\, 6}}{2} \)
Therefore: \(\displaystyle a + bi \;=....\)